(untitled) (Archives of Criminology, 2023)
This paper introduces the concept of algorithm-driven populism, considering whether it has a consonant or a conflicting relation with liberal democracy. The overall argument is that social media platforms are not just new media used by populists; algorithms have co-constituted a new form of populism. Based on a literature review that connected different fields of research together in order to elucidate the relation between populism and digital media, this article details a few important features of social media platforms, examining how they set up specific affordances that endanger the values of liberal democracy.